2015
DOI: 10.1016/j.anbehav.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Social rules govern vocal competition in the barn owl

Abstract: To resolve the share of limited resources, animals often compete through exchange of signals about their relative motivation to compete. When two competitors are similarly motivated, the resolution of conflicts may be achieved in the course of an interactive process. In barn owls, Tyto alba, in which siblings vocally compete during the prolonged absence of parents over access to the next delivered food item, we investigated what governs the decision to leave or enter a contest, and at which level. Siblings alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 49 publications
(52 reference statements)
2
18
1
Order By: Relevance
“…Extensive variation in playback loudness did not significantly influence the investment of barn owl nestlings in sibling competition, contrary to variation in call rate and duration (present study and Ruppli et al, 2013;Dreiss, Ruppli, Faller, et al, 2015). Call loudness had weak or no influence on the negotiation process, as the playback loudness treatment did not affect the key acoustic parameters (call rate and duration) used in sibling negotiation.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Extensive variation in playback loudness did not significantly influence the investment of barn owl nestlings in sibling competition, contrary to variation in call rate and duration (present study and Ruppli et al, 2013;Dreiss, Ruppli, Faller, et al, 2015). Call loudness had weak or no influence on the negotiation process, as the playback loudness treatment did not affect the key acoustic parameters (call rate and duration) used in sibling negotiation.…”
Section: Discussioncontrasting
confidence: 66%
“…When owlets are alone in the nest waiting for a parent to come back with a prey item, they continuously exchange hissing calls to advertise their hunger levels to siblings. Hungry individuals produce more calls and longer calls, which progressively deters their siblings from calling and competing for the food item next delivered by the parent (Dreiss, Ruppli, Faller, & Roulin, ; Ruppli, Dreiss, & Roulin, ). This communication system reduces the cost of sibling competition between related individuals (Johnstone & Roulin, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roulin et al (2000) first used the term of Bsibling negotiation^to describe the vocal interaction between siblings preceding a parental feeding event. In sibling negotiation, nestlings vocally interact in the absence of parents Dreiss et al 2015), which influences the outcome of the pending competition (Dreiss et al 2010b). Previous empirical work and theory concluded that sibling negotiation Bis more likely to prove stable when the food provided by parents is nondivisible^ (Johnstone and Roulin 2003).…”
Section: Rate Of Nestling Callsmentioning
confidence: 99%
“…For each individual, we broadcast 14 times in a row the same 45-min playback sequence, each sequence followed by 15 min of silence. Owlets react in a similar way in front of unfamiliar playback calls and live nestlings' calls (they avoid overlapping playback calls, Dreiss et al 2013b; they refrain from calling in front of a highly vocal playback, Ruppli et al 2013a; they insert their calls between playback calls in the same way they do with live nestlings, Dreiss et al 2015) and are not physiologically stressed in nest boxes placed in the laboratory (Dreiss et al 2010a). …”
Section: Playback Experimentsmentioning
confidence: 99%